2021
DOI: 10.1039/d1cp00337b
|View full text |Cite
|
Sign up to set email alerts
|

A robust, freeze-resistant and highly ion conductive ionogel electrolyte towards lithium metal batteries workable at −30 °C

Abstract: The wide applications of lithium metal batteries have encountered a severe conductivity issue when operating in cold weather. Here we report a freeze-resistant lithium metal battery, which displays outstanding rate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…Reproduced with permission. [ 6 ] Copyright 2021, Royal Society of Chemistry. E) Inhibitory capability of IL‐gels to bacteria ( E. coli , S. aureus , and B. subtilis ), fungus ( C. albicans ), and mold ( Asp.…”
Section: Il Endowing Gel Unique Functionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reproduced with permission. [ 6 ] Copyright 2021, Royal Society of Chemistry. E) Inhibitory capability of IL‐gels to bacteria ( E. coli , S. aureus , and B. subtilis ), fungus ( C. albicans ), and mold ( Asp.…”
Section: Il Endowing Gel Unique Functionsmentioning
confidence: 99%
“…The ionogel showed good conductivity, but the hydrogel has no conductivity. Tang et al [6] synthesized an ionogel by using [BMIM][BF 4 ] IL, which showed good self-healing capability at −30 °C, which can self-heal within 10 h without external stimuli (Figure 4D). These results prove that IL can endow the ionogels with good antifreezing capability.…”
Section: Excellent Properties In a Wide Temperature Rangementioning
confidence: 99%
See 2 more Smart Citations
“…They are also known as iongels, ionic liquid gels or ionogels if an IL-based electrolyte is used. [14] Although this approach is quite popular in Li-ion, [15][16][17] Li-metal, [18][19][20] sodiummetal [21,22] or other type of batteries, [8,23] it has not been largely explored for LiÀ O 2 cells. There are a few examples based on poly(methyl) methacrylate (PMMA) [24,25] or poly(vinylidene fluoride-co-hexafluoropropylene) (PVdF-HFP) [26,27] polymerbased iongels.…”
Section: Introductionmentioning
confidence: 99%